Depression in middle and older adulthood: the role of immigration, nutrition, and other determinants of health in the Canadian longitudinal study on aging - Davison, Karen M.; Lung, Yu; Lin, Shen (Lamson); Tong, Hongmei; Kobayashi, Karen M.; Fuller‑Thomson, Esme (My University, 2019)
Background: Little is known about depression in middle-aged and older Canadians and how it is affected by health determinants, particularly immigrant status. This study examined depression and socio-economic, health, immigration and nutrition-related factors in older adults. Methods: Using weighted comprehensive cohort data from the baseline Canadian Longitudinal Study on Aging (n = 27,162) of adults aged 45–85, gender-specific binary logistic regression was conducted with the cross-sectional data using the following variables: 1) Depression (outcome) measured using the Center for Epidemiologic Studies Short Depression (CESD-10) rating scale; 2) Immigration status: native-born, recent and mid-term (< 20 years), and long-term immigrants (≥20 years); and 3) covariates: socioeconomic status, physical health (e.g., multi-morbidity), health behavior (e.g., substance use), over-nutrition (e.g., anthropometrics), under-nutrition (e.g., nutrition risk), and dietary intake. Results: The sample respondents were mainly Canadian-born (82.6%), women (50.6%), 56–65 years (58.9%), earning between C$50,000–99,999 (33.2%), and in a relationship (69.4%). When compared to Canadian-born residents, recent, mid-term (< 20 years), and longer-term (≥ 20 years) immigrant women were more likely to report depression and this relationship was robust to adjustments for 32 covariates (adjusted ORs = 1.19, 2.54, respectively, p < 0.001). For women, not completing secondary school (OR = 1.23, p < 0.05), stage 1 hypertension (OR = 1.31, p < 0.001), chronic pain (OR = 1.79, p < 0.001), low fruit/vegetable intakes (OR = 1.33, p < 0.05), and fruit juice (OR = 1.80, p < 0.001), chocolate (ORs = 1.15–1.66, p’s < 0.05), or salty snack (OR = 1.19, p < 0.05) consumption were associated with depression. For all participants, lower grip strength (OR = 1.25, p < 0.001) and high nutritional risk (OR = 2.24, p < 0.001) were associated with depression. For men, being in a relationship (OR = 0.62, p < 0.001), completing postsecondary education (OR = 0.82, p < 0.05), higher fat (ORs = 0.67–83, p’s < 0.05) and omega-3 egg intake (OR = 0.86, p < 0.05) as well as moderate intakes of fruits/vegetables and calcium/high vitamin D sources (ORs = 0.71–0.743, p’s < 0.05) predicted a lower likelihood of depression. For men, chronic conditions (ORs = 1.36–3.65, p’s < 0.001), chronic pain (OR = 1.86, p < 0.001), smoking (OR = 1.17, p < 0.001), or chocolate consumption (ORs = 1.14–1.72, p’s < 0.05) predicted a higher likelihood of depression. Conclusions: The odds of developing depression were highest among immigrant women. Depression in middleaged and older adults is also associated with socioeconomic, physical, and nutritional factors and the relationships differ by sex. These results provide insights for mental health interventions specific to adults aged 45–85.
Keywords: older adults; middle-age; immigration; determinants of health; nutrition; CLSA; depression